Organizational (issue) field perspective on climate change - Achim Oberg; Lianne Lefsrud; Renate E. Meyer (economic sociology_the european electronic newsletter, 2021)
We are in crisis mode. Climate change is simultaneously the grandest global challenge and a daily challenge to individuals' perceptions, motivations, and actions. Economic sociology equips us to examine the heart of this crisis: the means, institutions, and regulations of production, exchange, and consumption. To complement this, we must have theoretical and methodological approaches that simultaneously bridge these macro-global and micro-actor levels. The aim of our article is to propose a research agenda for examining climate change from a field perspective to serve as this bridge. Institutional theory defines the "field" as a unit of analysis, rather than focusing on solo organizations or people, to examine all relevant players in processes of stability and change. This concept is influenced by Bourdieu's (1977) notion of "social field" or socially constructed arena: how organizations' interests and activities are mutually constituted through the interactions between them. In this article, we answer three questions regarding the theoretical, methodological, and empirical benefits of taking a field perspective. Why is this helpful for examining climate change? We start with a brief discussion of the relevance of organizations for influencing CO2 production and for contributing to discussions on climate change. We then discuss the relevance of examining relational interactions, between organizations, in stabilizing or changing current positions towards debated actions and towards daily production practices. How is this approach usefully different? We propose that by combining two types of fields - organizational fields and issue fields - we can examine the relationships between organizational actions and discourse. From this we can examine what organizations are doing, how they are "talking," and why they are influenced by this. How does this provide actionable insights? Finally, we demonstrate how both types of fields can be captured simultaneously via big data approaches - by accessing the websites of thousands of organizations and by extracting how they link to each other. Such a research approach helps to inform our understanding of climate change debates and practices, highlights barriers, and offers alternative solutions.
Keywords: 300